"Alexa, order me a pizza!": The mediating role of psychological power in the consumer–voice assistant interaction. Issue 7 (31st March 2021) - Tassiello, Vito; Tillotson, Jack S.; Rome, Alexandra S.
Abstract: This article investigates the consumer–voice assistant (VA) interaction in the context of food and beverage purchase choices and the role that psychological power plays in the consumer decision‐making process. A series of experimental studies demonstrate that both involvement and the psychological condition of power meditate consumers' willingness to purchase. As a result, we find that consumers are more likely to purchase low involvement than high‐involvement products through VA technology, particularly when experiencing high‐power states. This study broadens our understanding of the role of VAs and their ability to shape the consumer decision‐making process. With an explicit focus on power, this study illustrates how the success of voice commerce may largely rest on the promotion of low‐involvement products that enable high‐power psychological conditions which drive willingness to purchase.